Recessions and local labor market hysteresis - Brad Hershbein; Bryan A. Stuart (W.E. Upjohn Institute for Employment Research, 2020)
This paper studies the effects of each U.S. recession since 1973 on local labor markets. We find that recession-induced declines in employment are permanent, suggesting that local areas experience permanent declines in labor demand relative to less-affected areas. Population also falls, primarily due to reduced in-migration, but by less than employment. As a result, recessions generate long-lasting hysteresis: persistent decreases in the employment-to-population ratio and earnings per capita. Changes in the composition of workers explain less than half of local hysteresis. We further show that finite sample bias in vector autoregressions leads to artificial convergence, which can explain why some previous work finds no evidence of hysteresis in employment rates.
Keywords: I24; I26; J24; J31; 330; recessions; hysteresis; demand shocks; local labor markets; event study